New exploration on the philosophical examination of Chinese sportsmanship - Jia, Peng (2024)
Chinese sportsmanship is the essence of Chinese sports and national spirit, and the soul and essence of Chinese sports. In reality, people understand the sportsmanship as a form of exercise that is detached from the spiritual level, neglecting the spiritual value comparable to physical exercise, concealing its deep spiritual connotations and placing the spirit of sports in a corner, away from the “bravery of the soul and the vitality of the body” of sports. The philosophical foundation and historical development of Chinese sports spirit have been explored and examined, aiming to understand the profound connotation and value of Chinese sports spirit. Since the founding of the People’s Republic of China, the spirit of Chinese sports has played a special leading role in China, and has been widely recognized and affirmed by the Party Central Committee and various social classes. However, people’s understanding of it is not deep enough and is only in the preliminary research stage. In order to adapt to various needs, the in-depth exploration of the philosophical examination of Chinese sportsmanship has significant theoretical value and practical significance. The Chinese sports spirit is not only about physical exercise, but also emphasizes physical and mental harmony, both internal and external cultivation, and the pursuit of a state of physical and mental pleasure and comfort. The Chinese sports spirit is in line with traditional Chinese philosophical thoughts, such as “harmony between heaven and man” and social harmony.